Austen's Unbecoming Conjunctions - Heydt-Stevenson, J. author. aut Link
X, 275 p.
Keywords: Austen'sUnbecomingConjunctions is a contemporary study of all Jane Austen's writings focusing on her representation of women, sexuality, the material objects, and linguistic patterns by which this sexuality was expressed. Heydt-Stevenson demonstrates the subtle, vulgar, and humorous ways Austen uses human bodies, objects, and activities (fashion, jewelry, crafts, popular literature, travel and tourism, money, and courtship rituals) to convey sexuality and sexual appetites. Through the sexual subtext, Heydt-Stevenson proposes, Austen satirized contemporary sexual hypocrisy; overcame the stereotypes of women authors as sexually inhibited, sheltered, or repressed; and addressed as sophisticated and worldly an audience as Byron's. Thus through her careful reading of all the Austen texts in light of the language of eroticism, both traditional and contemporary, Heydt-Stevenson re-evaluates Austen's audience, the novels, and her role as a writer.